الاستصحاب ودوره في توجيه الشواهد النحوية والصرفية (al-ʾIstiṣḥāb and its Role in Explaining Syntax and Morphology Citations) - (Ibrahim Mohammed Abu al-Yazid Khafajah), إبراهيم محمد (مجلة الدراسات اللغوية والأدبية (Journal of Linguistic and Literary Studies), 2014)
ملخص البحث: تأثرت علوم اللغة العربية في نشأتها بالعلوم الشرعية وخاصة علم الفقه، حيث صاغ النحويون أصولهم النحوية على نمط الأصول الفقهية، وساروا على درب الفقهاء في ذلك، واتجه النحويون إلى الإغراق في التعليل والتأويل والجدل. وشغل البحث في أصول النحو حيزًا كبيرًا من تفكير علماء العربية، واستخدموا تلك الأصول في صوغ وتفسير القواعد التي تحكم اللسان العربي ومن بين تلك الأصول (الاستصحاب). وقد كان للاستصحاب مكانة متميزة في أصول النحو العربي على الرغم من مجيئه في مرتبة متأخرة بعد السماع والقياس، وهذا البحث محاولة للكشف عن هذا الدليل، وبيان مكانته بين أدلة النحو العربي، وعلاقته بقضاياه، وبيان دوره في تفسير وتوجيه عدد كبير من القضايا النحوية والصرفية والشواهد التي ثار حولها خلاف بين النحويين على اختلاف عصورهم ومذاهبهم واتجاهاتهم الفكرية، كذلك إلقاء الضوء على ما يقدمه هذا الدليل من معلومات تتعلق ببعض الشواهد التي وردت مستصحبة لأصولها، والتي عبرها ملاحظة التطور التاريخي للغة العربية ودراسة بعض مظاهره. الكلمات المفتاحية: الاستصحاب- الحال- الأصل- الفرع- الضرورة. Abstract: Arabic Language studies were been influenced in their formation with Islamic studies most especially Islamic Jurisprudence.(Al- Fiqh). The Arabic Grammarians designed their grammatical basis in line with jurisprudence’s. Arabic Grammarians followed Greek trends on their explanation, interpretations and argumentations. Research on formation of Arabic Grammar takes a vast place from reasoning of Arabic Language erudite thoughts. These fundamental basis were used for design and explanation of rules that monitor and judge Arabic Language. Among these basis is “Al- Istis haab” Conjunction. Despite its late arrival after “Sama’u” audible and “Qiyaas” analogy, this term retained a distinguished place in fundamental basis of Arabic Grammar. This research is going to explore this proof and emphasis its statue among Arabic Grammar guides, its relationship with some issues and elaborating its role in explanation and directing a vast number of Syntax and Morphology issues and citations that raised varieties among Grammarians irrespective of their eras, doctrines, and thoughts trends. And to shade more light and what this symptom contributes to knowledge, which are related to some grammatical evidences that have been found in accompany of these basis. Some noticeable and long aged development for Arabic Language and study of its phenomenon completed through it. Keywords: Conjunction- Condition- Foundation- Branch- Neccesity. Abstrak: Ilmu-ilmu bahasa Arab pada awalnya terpengaruh dengan ilmu-ilmu syariah khususnya Ilmu Fiqh. Para sarjana bahasa meletakkan kaedah tatabahasa mereka berdasarkan kepada format kaedah-kaedah Fiqh dan bersandarkan kepada pendekatan para Fuqaha’ dalam usaha mereka. Ini seterusnya menjadikan perbahasan bahasa menjadi begitu dalam kupasannya dengan pentakwilan yang pelbagai dan perbahasan yang berpanjangan. Kaedah-kaedah asal bahasa merupakan memonopoli perbahasan sarjana bahasa di waktu itu. Ia diguna pakai dalam menghuraikan kaedah-kaedah yang menjadi landasan bahasa Arab dan di antaranya ialah Istishab. Kaedah ini mempunyai kedudukannya yang tersendiri dalam tatabahsa Arab walaupun dari segi kedudukannya ia adalah selepas kaedah dengar dan qiyas. Kajian ini bertujuan menyingkap kaedah pemberian dalil ini, kedudukannnya dalam hirarki kaedah-kaedah utama bahasa dan juga isu-isu yang berkaitan. Peranannya dalam mencorakkan pengkaedahan beberapa isu tatabahasa dan morfologi serta masalah berbangkit yang menjadi perdebatan di antara sarjana bahasa yang berbeza-beza mazhab serta zamannya. Beberapa dalil yang dikemukakan oleh kaedah ini juga akan dianalisa sepanjang perkembangan pengkajian bahasa Arab dalam sejarahnya. Kata Kunci: Istishaab- Keadaan- kaedah tatabahasa- Cawangan- Keperluan.